Harnessing selenium nanoparticles (SeNPs) for enhancing growth and germination, and mitigating oxidative stress in Pisum sativum L. - Job T. Tendenedzai; Evans M. N. Chirwa; Hendrik G. Brink (Scientific Reports, 2023)
Abstract Selenium, an essential micronutrient for plants and animals, can cause selenium toxicity as an oxyanion or at elevated doses. However, the toxic selenite (SeO3 2−) oxyanion, can be converted into less harmful elemental nano-selenium (Se0), with various practical applications. This research aimed to investigate two methods for reducing SeO3 2−: abiotic reduction using cell-free extract from Enterococcus spp. (abiotic-SeNPs) and chemical reduction involving L-ascorbic acid (chemical-SeNPs). Analysis with XPS confirmed the presence of Se0, while FTIR analysis identified surface functional groups on all SeNPs. The study evaluated the effects of SeO3 2−, abiotic-SeNPs, and chemical-SeNPs at different concentrations on the growth and germination of Pisum sativum L. seeds. SeO3 2− demonstrated detrimental effects on germination at concentrations of 1 ppm (germination index (GI) = 0.3). Conversely, both abiotic- and chemical-SeNPs had positive impacts on germination, with GI > 120 at 10 ppm. Through the DPPH assay, it was discovered that SeNPs exhibited superior antioxidant capabilities at 80 ppm, achieving over 70% inhibition, compared to SeO3 2− (less than 20% inhibition), therefore evidencing significant antioxidant properties. This demonstrates that SeNPs have the potential to be utilized as an agricultural fertilizer additive, benefiting seedling germination and development, while also protecting against oxidative stress.